2020
DOI: 10.1128/aac.02129-19
|View full text |Cite
|
Sign up to set email alerts
|

A Biosynthetic Platform for Antimalarial Drug Discovery

Abstract: 14Advances in synthetic biology have enabled production of a variety of compounds using 15 bacteria as a vehicle for complex compound biosynthesis. Violacein, a naturally occurring 16 indole pigment with antibiotic properties, can be biosynthetically engineered in Escherichia 17 coli expressing its non-native synthesis pathway. To explore whether this synthetic 18 biosynthesis platform could be used for drug discovery, here we have screened bacterially-19 derived violacein against the main causative agent of h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Recently, we have generated a wide range of violacein and deoxyviolacein analogues from E. coli cells that were expressing a synthetic violacein biosynthesis pathway vioABCDE with added substituted tryptophans, and these crude extracts were tested against the malarial parasite Plasmodium falciparum . 24 Because of the promiscuity of the enzymes involved in the biosynthesis of violacein, we rationalized that a combination of enzymes from closely related bisindole biosynthesis pathways could generate compatible tryptophan analogues, leading to other interesting new-to-nature analogues of violacein that might otherwise be difficult to synthesize. Rebeccamycin is a closely related bisindole where the biosynthetic pathway contains several genes, including rebO (Q8KHS0) and rebD (Q8KHV6), which are homologous to vioA (Q9S3V1) and vioB (Q9S3V0), respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have generated a wide range of violacein and deoxyviolacein analogues from E. coli cells that were expressing a synthetic violacein biosynthesis pathway vioABCDE with added substituted tryptophans, and these crude extracts were tested against the malarial parasite Plasmodium falciparum . 24 Because of the promiscuity of the enzymes involved in the biosynthesis of violacein, we rationalized that a combination of enzymes from closely related bisindole biosynthesis pathways could generate compatible tryptophan analogues, leading to other interesting new-to-nature analogues of violacein that might otherwise be difficult to synthesize. Rebeccamycin is a closely related bisindole where the biosynthetic pathway contains several genes, including rebO (Q8KHS0) and rebD (Q8KHV6), which are homologous to vioA (Q9S3V1) and vioB (Q9S3V0), respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…We hypothesize that this is due to the preference of VioE in catalyzing the formation of 5′-Br-prodeoxyviolacein, in accordance with the isomer preference previously observed with various other violacein and deoxyviolacein analogues. 24 We then proceeded to screen a series of conditions that might facilitate Suzuki–Miyaura cross-coupling; however, because of low titers of 5′-bromo-violacein and 5′-bromo-deoxyviolacein available in the crude extract and challenges relating to the separation of these compounds that showed a propensity for pi-stacking, the isolation of products for further characterization and bioassays of the cross-coupling product proved difficult. We thus focused on systemically identifying conditions that would allow direct cross-coupling in crude extracts, which identified the optimal conditions for derivatization.…”
Section: Results and Discussionmentioning
confidence: 99%
“…A recent study showed that violacein induces aggregation of actin in Plasmodium without affecting actin polymerization. 70 The study suggests that violacein might be interacting with actin indirectly via actin binding partners or by disturbing actin folding pathway. We propose that violacein disrupts the Plasmodium foldosome, in which Hsp70 and Hsp90 are critical players for the survaillance of protein folding, trafficking, quality control, and degradation processes.…”
Section: Discussionmentioning
confidence: 97%
“…It was found that the nature of substituents on the aromatic ring greatly influenced the antiprotozoal activity and further confirmed that the enzyme PfDHODH was the target of these compounds. Violacein, an indole pigment synthetically engineered from E. coli, was found to significantly affect the P. falciparum actin cytoskeleton [ 38 ]. Many traditional methods of antimalarial drug discovery such as optimization of existing therapy, analogue of existing therapy, drug resistance reversers and active compounds against new targets are known.…”
Section: Malaria As a Global Challengementioning
confidence: 99%